A NEW CEPHALOPOD FROM THE EARLY SILURIAN OF THE CARNIC ALPS (ITALIAN SIDE) (Rivista italiana di Paleontologia e Stratigrafia, 2022)
A new Early Silurian cephalopod from the Italian side of the Carnic Alps is reported on the basis either of newly collected material or museum specimens. The genus Serpaglioceras gen. nov. and the species S. forojuliense sp. nov. are described. The material described originates from the Pterospathodus celloni biozone.